2011
DOI: 10.1007/s11357-011-9327-0
|View full text |Cite
|
Sign up to set email alerts
|

Genes and the ageing muscle: a review on genetic association studies

Abstract: Western populations are living longer. Ageing decline in muscle mass and strength (i.e. sarcopenia) is becoming a growing public health problem, as it contributes to the decreased capacity for independent living. It is thus important to determine those genetic factors that interact with ageing and thus modulate functional capacity and skeletal muscle phenotypes in older people. It would be also clinically relevant to identify 'unfavourable' genotypes associated with accelerated sarcopenia. In this review, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 138 publications
1
68
0
2
Order By: Relevance
“…However, others have shown that myostatin expression does not increase (Kawada et al 2001;Welle et al 2002), and can even decrease (Baumann et al 2003), in ageing-induced sarcopenia in humans or rodents, thus questioning its involvement in muscle mass wasting during ageing. In fact, the R allele has not been associated with higher muscle mass/function in old Caucasian people (aged <80 years) (see Garatachea and Lucía (2013) for a review). Carriage of one R allele does not seem to exert a major influence in the muscle phenotypes of non-agenarians (Gonzalez-Freire et al 2010) whereas, surprisingly, the only two reported Caucasian old people with the RR genotype (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have shown that myostatin expression does not increase (Kawada et al 2001;Welle et al 2002), and can even decrease (Baumann et al 2003), in ageing-induced sarcopenia in humans or rodents, thus questioning its involvement in muscle mass wasting during ageing. In fact, the R allele has not been associated with higher muscle mass/function in old Caucasian people (aged <80 years) (see Garatachea and Lucía (2013) for a review). Carriage of one R allele does not seem to exert a major influence in the muscle phenotypes of non-agenarians (Gonzalez-Freire et al 2010) whereas, surprisingly, the only two reported Caucasian old people with the RR genotype (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The Lys(K)153Arg(R) amino acid replacement is found within the active mature peptide of the myostatin protein; it could influence proteolytic processing with its pro-peptide or affinity to bind with the extracellular activin type II receptor (ActRIIB). The MSTN K153R polymorphism is thus a candidate to influence skeletal muscle phenotypes, included in old people (see Garatachea and Lucía (2013) for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, for regulatory genes, low expression indices may be enough for a major impact on the size and structure of the muscle (Braun & Gautel, 2011). We also based our choice of the studied genes on known data for farm animals about their impact on the quality of meat (Kogelman et al, 2011), and the information of the impact on muscle growth in humans and laboratory animals (Braun & Gautel, 2011;Garatachea & Lucía, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…ACTN3 is located in the Z-line inside muscle cells, where it helps to anchor actin filaments 9 . R577X polymorphism in the ACTN3 gene is classified as nonsense, in which there is an exchange of C à T nucleotide at position 1747 of the exon 16 , resulting in the exchange of the triplet of nucleotides responsible for the translation of arginine -then becoming a stop codon or triplet, generating a truncated protein. Individuals who have the XX genotype have lack of ACTN3, while heterozygotes (RX genotype) have fewer amount of ACTN3, but no disease 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The elderly population is growing worldwide and also in Brazil, and there are very few surveys seeking to associate genetic variations in ACE and ACTN3 to physical fitness in the elderly [14][15] , especially in the Brazilian population [16][17] . Studies on this issue are primarily justified for showing the influence of genetics on physical fitness in the elderly in order to identify the loss of physical fitness before the individual gets old, which can harm ordinary activities of the daily living and provide data that can justify and contribute to future studies aimed at determining whether genetic polymorphisms may influence the magnitude of the response to interventions with exercise.…”
Section: Introductionmentioning
confidence: 99%